2018
DOI: 10.1080/01658107.2018.1482358
|View full text |Cite
|
Sign up to set email alerts
|

Complete recovery of filler-induced visual loss following subcutaneous hyaluronidase injection

Abstract: The rise in popularity of hyaluronic acid (HA) dermal filler injection has caused an exceptional increase in the number of cases of reported irreversible blindness. Here, we reported a case of ischemic optic neuropathy and ophthalmoplegia following subcutaneous HA filler injection with complete visual recovery. A 31-year-old Chinese woman presented with sudden onset of right monocular visual impairment associated with diplopia. Patient had received a hyaluronic acid-containing filler injection for nasal dorsum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Treatment should be extremely timely because time to reverse the blindness is short. There is very limited evidence to support intervention but both supratrochlear, 17 supraorbital, 16 and dorsal nasal vascular access 33 treatments and retrobulbar injections 15 have had some limited success.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment should be extremely timely because time to reverse the blindness is short. There is very limited evidence to support intervention but both supratrochlear, 17 supraorbital, 16 and dorsal nasal vascular access 33 treatments and retrobulbar injections 15 have had some limited success.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that in the case of embolism caused by HA, hyaluronidase given within the window period of 60–90 min has a strong chance of dissolving HA embolism. 42 Another series of 6 cases of vision loss caused by HA filler injection showed improved visual acuity or complete reversal in 4 of the cases. The authors suggested that early supratrochlear/supraorbital hyaluronidase injection, ocular massage, and rebreathing into a plastic bag can be safe, uncomplicated and effective methods to enable restoration of the retinal circulation, and reverse vision loss.…”
Section: Discussionmentioning
confidence: 94%
“…In 2018, a case reported by Sharudin et al 42 showed a complete visual recovery of posterior ischemic optic neuropathy with ophthalmoplegia caused by HA filler injection. It has been suggested that in the case of embolism caused by HA, hyaluronidase given within the window period of 60–90 min has a strong chance of dissolving HA embolism.…”
Section: Discussionmentioning
confidence: 98%
“…High-level evidence is lacking for management (Tables 3 and 4), yet, limited reports of improvement of visual acuity after complete and partial vision loss secondary to filler injection exist. 4,45 50,57 A consensus opinion regarding the treatment of visual loss secondary to aesthetic intervention was recently published, suggesting a combination therapy using several retinal arterial vasodilators as well as anterior chamber paracentesis to decrease intra-ocular pressure. 9 Regarding hyaluronidase, although the level of evidence is low, if administration is to be performed, repeated injections in peribulbar approach is considered to be safer than retrobulbar injection.…”
Section: Resultsmentioning
confidence: 99%
“…Complete resolution of symptoms was documented in 7 patients, among which, 6 patients initially presented with partial vision loss or blurry vision, 4,[48][49][50]57 and only in 1 case, a reverse of complete vision loss was achieved by the unique combination of fast intervention along with hyaluronidase "flooding" approach. 45 Where full recovery was achieved, in 5 cases the initial intervention was immediate, 45,48,49,57 in 1 case the intervention took place 12 hours after injection 50 and in another case the timing of the initial intervention was not documented. 4 Although not resulting in full recovery, 1 report of reversing complete vision loss to return of ability to follow hand movement was reported.…”
Section: Discussionmentioning
confidence: 99%